Sacrococcygeal teratoma: Clinical characteristics, management, and long-term outcomes in a prospective study from a Tertiary Care Center - Devendra Kumar Yadav; Samir Kant Acharya; Deepak Bagga; Vishesh Jain; Anjan Dhua; Prabudh Goel (Wolters Kluwer Medknow Publications, 2020)
Introduction: The study focuses on the clinical presentation, management, and outcomes (both short term and long term) in patients with sacrococcygeal teratoma managed over a decade in a tertiary care center. Materials and Methods: This is a prospective study on children with sacrococcygeal teratoma over 12 years data collected included antenatal diagnosis, mode of delivery, age at diagnosis, clinical presentation, physical extent of mass (including Altman classification), levels of alpha-fetoprotein, surgical approach, histopathology, clinical outcome, recurrence and long-term results including bladder-bowel dysfunction and neurological impairment. Functional results were evaluated clinically and radiologically. Results: During the study, 41 patients (male to female ratio of 1:3.1) with a median age of 36 days (1 day-11.6 years) with sacrococcygeal teratoma were managed at our center. The mean follow-up duration was 54 months (range 19-110 months). Nearly, two-thirds of the tumors were either Altman Type 1 or 2. Yolk sac tumor was present in 8 (19.5%) patients, while the rest has either mature or immature teratoma. Tumors were removed through a posterior sagittal or a chevron incision. In seven patients, abdominosacral approach was necessary. Eight patients with malignant disease received chemotherapy (neoadjuvant in 5). Overall survival was 95% at a mean follow-up of 54 months. Among the late complications, three patients had a local recurrence of tumor, and urinary dribbling was present in three patients. Conclusions: Teratomas are the most common germ cell tumors of the sacrococcygeal region. Most of the tumors are benign, and the incidence of malignancy increases with age. The evaluation of malignancy is, therefore, necessary in these children. Excellent survival of 95% was achieved in this series. Morbidity due to associated malformation, disease recurrence, and treatment may persist in these patients; hence, proper follow-up is needed.